2021
DOI: 10.1161/strokeaha.120.032066
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neurological Improvement After Full Endovascular Reperfusion in Acute Anterior Circulation Ischemic Stroke

Abstract: Background and Purpose: We aimed to determine the prevalence and predictors of delayed neurological improvement (DNI) after complete endovascular reperfusion in anterior circulation acute ischemic stroke (AIS). Methods: Retrospective analysis of an online multicenter prospective reperfusion registry of patients with consecutive anterior circulation AIS treated with endovascular thrombectomy (EVT) from January 2018 to June 2019 in tertiary stroke centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Recent studies suggest that better neurological status at admission, male sex, and intravenous thrombolysis might increase probability of delayed neurological improvement. 11 Our subgroup analysis confirms these results and furthermore underlines the relevance of comorbidities such as diabetes, hypertension, dyslipidemia, and atrial fibrillation. Results suggest that these factors are not fully apparent in the early neurological status and might impact the course of the neurological recovery.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies suggest that better neurological status at admission, male sex, and intravenous thrombolysis might increase probability of delayed neurological improvement. 11 Our subgroup analysis confirms these results and furthermore underlines the relevance of comorbidities such as diabetes, hypertension, dyslipidemia, and atrial fibrillation. Results suggest that these factors are not fully apparent in the early neurological status and might impact the course of the neurological recovery.…”
Section: Discussionsupporting
confidence: 83%
“…Nonetheless, one quarter of these patients still achieves favourable functional outcome at 90 days follow-up [25][26][27]. Recent analyses suggest that better neurological status at admission, male sex and administration of IVT might increase probability of delayed neurological improvement in ACS [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focusing on ACS observed that approximately one quarter of patients experiences no early clinical improvement after successful recanalization. Nonetheless, one quarter of these patients still achieves favourable functional outcome at 90 days follow‐up [25‐27]. Recent analyses suggest that better neurological status at admission, male sex and administration of IVT might increase probability of delayed neurological improvement in ACS [25].…”
Section: Discussionmentioning
confidence: 99%
“…An increase by 4 or more points of NIHSS score was indicative of END. In patients who underwent rescue EVT, ENI and END were defined as improvement and worsening, respectively, of NIHSS score by more than 4 points after EVT in comparison with scores immediately before EVT [16]. All patients were clinically monitored until day 90 after EVT.…”
Section: Outcome Variablesmentioning
confidence: 99%